ANALISIS PENGARUH BUDAYA ORGANISASI, KEPEMIMPINAN DAN WORK LIFE BALANCE TERHADAP KINERJA PEGAWAI KANTOR PERWAKILAN BANK INDONESIA PROVINSI RIAU - Fahmi Irsyad; Susi Hendriani; Sukirno Putro (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2022)
This study aims to analyze the influence of organizational culture, leadership, and work life balance on employee performance at the Representative Office of Bank Indonesia, Riau Province. This research method is quantitative. The population in this study is the entire number of employees at the Representative Office of Bank Indonesia, Riau Province. The sampling technique in this research is using saturated sampling so that the number of samples is the same as the total population of 40 people. Analysis of the data in this study using multiple linear regression using a computer program. The results showed that there was an influence of organizational culture, leadership, and work life balance on employee performance at the Representative Office of Bank Indonesia, Riau Province. This study provides recommendations to the Representative Office of Bank Indonesia Riau Province to improve employee performance from indicators of innovation made by employees at work and indicators of employee development in addition to organizational culture that still needs to improve attitudes towards risk, action orientation, and power discance, on leadership variables it is necessary to paying attention to indicators of participation in decision making, and showing concern or interaction with the team, as well as on work life balance variables in almost all indicators such as work interfering with personal life, personal life interfering with work, satisfaction with work balance and improvisation of effectiveness at work.